Anomalous origin of the left coronary artery with origin in the right coronary artery from a single coronary ostium associated with multivessel coronary artery disease: case report and literature review - Castro-Lara, Jovany; Herrera-Lemus, Sara S.; Sánchez-Cassio, Sandra; Vera-Fuentes, Manuel A.; Vivas-Baizabal, Marco G.; Andrade-Torres, Erick G. (International Journal of Research in Medical Sciences, 2024)
The anomalous origin of the coronary arteries is a group of rare congenital heart conditions in which there has been an increase in its diagnosis thanks to more accessible and less invasive imaging techniques such as coronary angiotomography, which allows visualization of the arteries in its entire path in a short exploration interval, with adequate spatial and temporal resolution. The clinical presentation is variable, up to 80% are asymptomatic and the remaining 20% may present arrhythmias, myocardial infarction, heart failure and sudden death. We present the case of a patient with unstable angina in whom an anomalous origin of the left coronary artery (LCA) with origin in the right coronary artery (RCA) from a single coronary ostium associated with multivessel coronary artery disease was diagnosed.